Cultural Adaptation in Translation: A Comparative Analysis of “A Space for the Unbound” from Indonesian to English - Don Evan Hernando; Sulamit Syeba; Emeral Emeral; Dominggus Florensius; Arya Febridinata (Journal of Linguistics and Social Studies, 2026)
This study examines the translation of culture-specific items (CSIs) in A Space for the Unbound, an Indonesian adventure game localized into English. Using Vinay and Darbelnet's (1995) translation procedures as the analytical framework, supplemented by Baker's (1992) concept of cultural substitution, the study analyzes thirty-two CSIs drawn from Chapter 1 of the game, categorized into honorific titles, idioms, question tags, humor, sarcasm, slang, figurative language, and proverbs. Data were collected through comparative analysis of the Indonesian source text and its English localization. Findings show that cultural substitution was the dominant strategy, applied across most categories, while functional equivalence appeared in slang exclamations, literal translation in proverbs, and omission and addition in question tags. These results confirm a broadly domesticating orientation in the translation and contribute to the limited body of research on CSI translation in Indonesian-language video games.